Pre-service Teachers’ Beliefs about Moral Aspects of Teaching - Rajashree (Voices of Teachers and Teacher Educators, 2025)
This paper examines the beliefs of pre-service teachers about the moral work of teaching. A short questionnaire containing open-ended questions and an interview were used in the data-collection process of this research. Sixty student teachers from secondary teacher education institutions answered the questionnaire. Twenty of these student teachers were selected for in-depth interviews. Three categories of beliefs, namely psychological, educational and teaching beliefs of the pre-service teachers were analyzed in relation to the moral work of teaching. The pre-service teachers’ articulation of beliefs, not only indicate the presence of moral language but also reveal their desire and motivation to engage with moral work of teaching. The paper recommends the need for teacher educators to pay attention to the moral work of teaching in the pre-service teacher education programme.